MnZn-BASED FERRITE AND METHOD OF PRODUCING THE SAME

By optimizing the composition and firing process of MnZn-based ferrites with controlled grain size and reduced intragranular pores, the ferrite achieves enhanced magnetic properties for effective noise suppression in automotive electronics.

JP2024178781AActive Publication Date: 2024-12-25JFE CHEMICAL CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023097193
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2024-12-25
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

Conventional MnZn-based ferrites face challenges in maintaining high initial magnetic permeability in low frequency bands while achieving high normalized impedance in high frequency bands, especially when exposed to wide temperature variations, which is crucial for noise suppression in automotive electronics.

Method used

The solution involves controlling the crystal grain size and minimizing intragranular pores by adjusting the composition and temperature increase rate during the firing process, using specific ratios of Fe2O3, ZnO, MnO, SiO2, CaCO3, Nb2O5, Bi2O3, and V2O5, and optimizing the firing conditions to achieve a MnZn-based ferrite with enhanced magnetic properties.

Benefits of technology

The resulting MnZn-based ferrite exhibits high initial permeability across a wide frequency band of 10 to 500 kHz, large ΔB at high temperatures, and significant normalized impedance in the 500 kHz to 3 MHz range, making it suitable for high-temperature and high-frequency noise suppression applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178781000001
    Figure 2024178781000001
Patent Text Reader

Abstract

To provide a MnZn-based ferrite excellent in magnetic properties.SOLUTION: There is provided a MnZn-based ferrite in which a basic component is iron: 51.0-54.0 mol% as Fe2O3, zinc: 15.5-21.0 mol% as ZnO, and manganese: balance; an accessory component contains, with respect to the basic component, Si: 25 mass ppm or more and less than 50 mass ppm as SiO2, Ca: 500 mass ppm or more and 1,500 mass ppm or less as CaCO3, Nb: 50 mass ppm or more and 500 mass ppm or less as Nb2O5, Bi: 50 mass ppm or more and 700 mass ppm or less as Bi2O3, and V: 50 mass ppm or more and 500 mass ppm or less as V2O5; the number of pores occurring within crystal grains with respect to the number of total pores occurring in the MnZn-based ferrite is 20.0% or less; and an average crystal grain size is 16 μm or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an MnZn-based ferrite having improved magnetic properties and a method for producing the same. [Background technology]

[0002] MnZn ferrite, a representative soft magnetic material, is widely used in power transformers in switching power supplies and in noise suppression components. In particular, MnZn ferrite used as a noise suppression component is required to have high magnetic permeability, and is used as a common mode choke that removes unnecessary electrical components (noise) in all electronic devices such as air conditioners, televisions, and computers.

[0003] In recent years, the electrification of cars has progressed, and the demand for MnZn ferrites in the field of car electronics is growing. For in-vehicle applications, the temperature around the engine room ranges widely from -40℃ to 150℃, so MnZn ferrites that show stable properties over a wide temperature range are required.

[0004] Conventional MnZn ferrite has a saturation magnetic flux density of about 440 mT at room temperature and about 250 mT at 100°C. In addition, ΔB, which is the difference between the saturation magnetic flux density and the residual magnetic flux density at 100°C, is about 190 mT in conventional MnZn ferrite, so that loss increases at high temperatures. Therefore, when conventional MnZn ferrite is used for noise filters, it generates heat in the operating environment. Considering the effect on pulse noise generated by inverters and compressors, MnZn ferrite with a high ΔB value is required so that it can be used stably even at high temperatures.

[0005] Furthermore, to function as a common mode choke for noise filters, a normalized impedance that is sufficiently larger than the noise to be removed in the frequency band of the noise is required. In recent years, power semiconductors such as silicon carbide (SiC) and gallium nitride (GaN) have begun to be introduced as semiconductors for electric vehicles, but these power semiconductors generate large noise in the high frequency band of 1 MHz or more. Therefore, when used together with power semiconductors, MnZn ferrites that show a high normalized impedance that can remove noise in the high frequency band are required.

[0006] MnZn ferrite is inexpensive compared to amorphous metals and is therefore easy to introduce as a noise filter. 2+ Since the content of Fe is high, 3+ -Fe 2+ Since electrons are easily exchanged between the ferrites, the resistivity is low, on the order of 0.1 Ω·m. Because the resistivity is low, as the frequency band used becomes higher, the loss due to eddy currents in the MnZn ferrite increases rapidly, and the initial permeability decreases. As the initial permeability decreases, the inductance decreases, and at the same time, the maximum value of the standardized impedance decreases and the frequency at which the standardized impedance is maximum becomes lower. Therefore, in order to obtain a high standardized impedance in the high frequency band, a resistivity of 10 5 NiZn ferrite, which has a high resistivity of Ω·m or more among ferrites, is used, or MnZn ferrite, which has a high resistivity of Ω·m or more. 2+ It was necessary to reduce the amount of SiO2 to increase the resistivity.

[0007] However, when NiZn ferrite is used, the initial permeability in the low frequency band is low at around several hundred, making it unsuitable for common mode chokes. On the other hand, in the case of MnZn ferrite, the Fe 2+However, there is a problem that reducing the amount of metal oxide reduces the magnetic moment and the saturation magnetic flux density. Therefore, another method of increasing the resistivity is to add a small amount of metal oxide. Metal oxides other than the main component do not exhibit electrical conductivity and segregate to the grain boundaries in the crystal structure, so adding metal oxide increases the grain boundary resistance, and can increase the resistivity of MnZn ferrite.

[0008] Patent Document 1 shows that the addition of Nb2O5 and V2O5 reduces the residual magnetic flux density and improves ΔB. Patent Document 2 discloses MnZn-based ferrite containing one or more elements selected from Zr, Nb, Co, Ti, Ta, V, Bi, Mo, Sn, Li, Mg, and Al for the purpose of improving the strength of the sintered body. Patent Document 3 discloses MnZn-based ferrite in which magnetic loss and power loss are reduced by adding SiO2 and CaO. Patent Document 4 discloses a method for producing MnZn-based ferrite with high initial permeability in which the crystal grain size is increased by adjusting the heating rate of 350°C / hr or more and the oxygen concentration during the heating process, and no vacancies remain in the crystal grains. Patent Document 5 discloses MnZn-based ferrite in which the number of voids in the crystal grains is less than 40% of the total number of voids (air holes) in the MnZn-based ferrite. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 6-283320 [Patent Document 2] JP 2014-080344 A [Patent Document 3] JP 2001-342058 A [Patent Document 4] JP 2009-173474 A [Patent Document 5] International Publication No. 2020 / 158333 Summary of the Invention [Problem to be solved by the invention]

[0010] However, when a small amount of metal oxide is added to increase resistivity in order to improve normalized impedance and ΔB at high frequencies, there is a problem that the initial permeability at low frequencies of about 10 kHz decreases. In order to use MnZn ferrite as a common mode choke, it is necessary for it to have a high initial permeability, and conventional technology has not been able to improve normalized impedance and ΔB at high frequencies while suppressing the decrease in initial permeability at low frequencies.

[0011] The invention described in Patent Document 1 is applied to MnZn-based ferrite used as a magnetic core for power transformers, and does not mention the initial magnetic permeability as a high magnetic permeability material. In general, when an additive is added to increase the resistivity, the initial magnetic permeability in a low frequency band of about 10 kHz decreases, so the addition of only Nb2O5 and V2O5 does not ensure sufficient initial magnetic permeability, and it can be said that it is unsuitable as a ferrite for noise suppression. In addition, the inventions described in Patent Document 2 and Patent Document 3 are not aimed at improving ΔB and normalized impedance. In Patent Document 4, the specific ratio of intragranular pores is not shown, and it is considered that there is a limit to the reduction of intragranular pores when the heating rate is 350°C / hr or more. In addition, there is no mention of ΔB, and only the impedance value at 150 kHz is disclosed, and noise removal characteristics in a frequency band higher than 150 kHz are not guaranteed. In Patent Document 5, although the reduction of pores in crystal grains is mentioned, it is applied to MnZn-based ferrite used as a magnetic core for power transformers, and the initial magnetic permeability is not mentioned. In addition, since it does not contain the additive V2O5 that reduces the residual magnetic flux density, it does not obtain a sufficient ΔB and is therefore unsuitable as a noise filter.

[0012] The present invention has been developed in view of the above circumstances, and aims to provide an MnZn-based ferrite having a high initial permeability in a wide frequency band of 10 to 500 kHz, a large ΔB even at a high temperature such as 100°C, and a large maximum value of normalized impedance in a high frequency band of 500 kHz to 3 MHz, and an advantageous method for producing the same. [Means for solving the problem]

[0013] The inventors of the present invention have made extensive research to solve the above problems, and have found the following. Initial permeability is an index that indicates the ease of movement of "domain walls," which are the boundaries of regions where magnetic moments facing the same direction are gathered, called magnetic domains. If the crystal grain size is large, the magnetic domains are also large, and if there are few pores in the crystal grains, there is nothing to hinder the movement of the domain walls, so the domain walls move more easily and the initial permeability is high. Therefore, in order to prevent a decrease in the initial permeability in the low frequency band, it is important to increase the crystal grain size of the MnZn ferrite and reduce the pores in the crystal grains as much as possible. In order to obtain such a crystal structure, it is important to control the content of the subcomponents within a predetermined range and to control the heating rate during sintering. In particular, it is important to slow down the heating rate in order to reduce the pores in the crystal grains. If the heating rate is too fast, the pores that were at the grain boundaries in the early sintering stage are taken into the grains as the crystal grains grow, and remain as pores in the grains.

[0014] The present invention, which has been completed based on the above findings, has the following essential features.

[0015] [1] A MnZn-based ferrite consisting of basic components, auxiliary components and unavoidable impurities, The basic components are calculated as Fe2O3, ZnO, and MnO, with the total of iron, zinc, and manganese being 100 mol%, Iron: 51.0 mol% or more and 54.0 mol% or less in terms of Fe2O3, Zinc: 15.5 mol% or more and 21.0 mol% or less in terms of ZnO, and Manganese: Remainder and With respect to the basic component, the subcomponent is Si: 25 mass ppm or more and less than 50 mass ppm in terms of SiO2, Ca: 500 mass ppm or more and 1500 mass ppm or less in terms of CaCO3; Nb: 50 mass ppm or more and 500 mass ppm or less in terms of Nb2O5, Bi: 50 ppm by mass or more and 700 ppm by mass or less in terms of Bi2O3, and V: 50 ppm by mass or more and 500 ppm by mass or less in terms of V2O5 Including, The number of pores generated within crystal grains is 20.0% or less of the total number of pores generated in the MnZn-based ferrite, MnZn ferrite with an average crystal grain size of 16 μm or more.

[0016] [2] The Mn-Zn ferrite according to the above [1], having a value of ΔB [mT] calculated by the following formula (1) of 215 mT or more at 100° C. ΔB=B m -B r (1) However, B m is the saturation magnetic flux density [mT], B r is the residual magnetic flux density [mT].

[0017] [3] In the frequency range of 500 kHz to 3 MHz, the standardized impedance Z is calculated using the following formulas (2) and (3). norm [Ω mm -1 ] maximum value is 30Ω·mm -1 The MnZn-based ferrite according to the above [1] or [2]. Z norm =Z c1 / N 2 (2) c1=l e / A e (3) where Z is the impedance [Ω] and c1 is the core constant [mm -1 ], l e is the magnetic path length [mm], A e is the cross-sectional area [mm 2], and N is the number of turns in the coil [-].

[0018] [4] The Mn-Zn-based ferrite according to any one of the above [1] to [3], wherein μi' (the real part of the initial magnetic permeability μi) at 10 kHz and 23° C. is 9000 or more, μi' (the real part of the initial magnetic permeability μi) at 500 kHz and 23° C. is 4000 or more, and the Curie temperature is 150° C. or more.

[0019] [5] Sintered density is 5.00g / cm 3 The MnZn-based ferrite according to any one of the above [1] to [4].

[0020] [6] A method for producing the MnZn-based ferrite according to any one of the above [1] to [5], a mixing and calcining step of mixing the basic components to obtain a first mixture and calcining the first mixture to obtain a calcined product; a mixing and grinding step of adding and mixing the auxiliary component with the calcined product to obtain a second mixture, and grinding the second mixture to obtain a ground product; A granulation step of adding and mixing a binder to the pulverized material, and then granulating the mixture to obtain a granulated powder; a molding step of molding the granulated powder to obtain a molded body; a firing step of firing the molded body under conditions in which the rate of temperature rise from 400° C. to the maximum temperature is 50° C. / hr or more and less than 300° C. / hr to obtain the MnZn-based ferrite; The present invention relates to a method for producing MnZn-based ferrite having the above structure.

[0021] [7] The method for producing MnZn-based ferrite according to [6] above, wherein the maximum temperature in the firing step is 1370°C or higher and 1450°C or lower. Effect of the Invention

[0022] The MnZn-based ferrite of the present invention has a high initial permeability in a wide frequency band of 10 to 500 kHz, a large ΔB even at a high temperature such as 100°C, and a large maximum value of normalized impedance in a high frequency band of 500 kHz to 3 MHz. Such MnZn-based ferrite can be used as a common mode choke that can handle high temperatures and high frequency bands. In addition, according to the manufacturing method of the MnZn-based ferrite of the present invention, it is possible to manufacture MnZn-based ferrite having the above-mentioned excellent magnetic properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Hereinafter, an embodiment of the MnZn ferrite and the manufacturing method thereof according to the present invention will be described. Note that the embodiment described below is an example of the present invention, and the configuration of the present invention is not limited to the specific example.

[0024] [MnZn ferrite] The MnZn ferrite according to the present invention is composed of basic components, subcomponents and unavoidable impurities, and the basic components are oxides of Fe, Zn and Mn. Note that the following mol% is the composition ratio in the basic components.

[0025] (Main component) Fe: 51.0-54.0 mol% When the Fe content of the MnZn ferrite is less than 51.0 mol% in terms of Fe2O3, the initial permeability and Curie temperature at room temperature decrease. mdecreases and sufficient ΔB cannot be obtained. Therefore, the Fe contained in the MnZn ferrite is 51.0 mol% or more, preferably 52.0 mol% or more, and more preferably 52.5 mol% or more, calculated as Fe2O3. On the other hand, if the Fe contained in the MnZn ferrite exceeds 54.0 mol% calculated as Fe2O3, the initial permeability at room temperature decreases, making it unsuitable for high permeability material applications, and the loss components increase, resulting in a large relative loss coefficient tanδ / μi. Therefore, the Fe contained in the MnZn ferrite is 54.0 mol% or less, calculated as Fe2O3, preferably 53.9 mol% or less, and more preferably 53.8 mol% or less.

[0026] Zn: 15.5-21.0mol% If the Zn content in the MnZn ferrite is less than 15.5 mol% in terms of ZnO, the resistivity of the MnZn ferrite decreases, resulting in poor characteristics in the high frequency band. Therefore, the Zn content in the MnZn ferrite is set to 15.5 mol% or more in terms of ZnO, preferably 16.0 mol% or more, and more preferably 18.0 mol% or more. On the other hand, if the Zn content in the MnZn ferrite exceeds 21.0 mol% in terms of ZnO, the B content of the MnZn ferrite increases. m Therefore, the amount of Zn contained in the MnZn ferrite is set to 21.0 mol % or less, preferably 20.8 mol % or less, and more preferably 20.7 mol % or less, calculated as ZnO.

[0027] Mn: remainder In the present invention, in order to obtain a sufficient initial magnetic permeability, the remainder of the basic components contained in the MnZn ferrite is Mn. For example, if the remainder of the basic components contained in the ferrite is Ni, a sufficient initial magnetic permeability cannot be obtained. The Mn contained in the MnZn ferrite is preferably 23.0 mol% or more, more preferably 25.0 mol% or more, and even more preferably 26.0 mol% or more, calculated as MnO. The Mn contained in the MnZn ferrite is preferably 30.0 mol% or less, more preferably 29.5 mol% or less, and even more preferably 29.3 mol% or less, calculated as MnO.

[0028] (Secondary ingredient) Next, the auxiliary components will be described. In the present invention, the content of the auxiliary components is the content relative to the basic component.

[0029] Si: 25 mass ppm or more and less than 50 mass ppm SiO2 segregates at grain boundaries in the crystal structure, improves the resistance of the grain boundaries, and improves the initial magnetic permeability and normalized impedance in the high frequency band. When the Si contained in the MnZn-based ferrite is less than 25 mass ppm in terms of SiO2, the initial magnetic permeability of the MnZn-based ferrite in the high frequency band is insufficient. Therefore, the Si contained in the MnZn-based ferrite is 25 mass ppm or more, preferably 27 mass ppm or more, in terms of SiO2. On the other hand, when the Si contained in the MnZn-based ferrite is 50 mass ppm or more in terms of SiO2, abnormal grain growth is caused, and the initial magnetic permeability of the MnZn-based ferrite in the low frequency band is significantly reduced. Therefore, the Si contained in the MnZn-based ferrite is less than 50 mass ppm in terms of SiO2, preferably 40 mass ppm or less, more preferably 39 mass ppm or less.

[0030] Ca:500~1500 mass ppm CaCO3 segregates at grain boundaries in the crystal structure, improves the resistance of the grain boundaries, and improves the initial magnetic permeability and normalized impedance in the high frequency band. When the Ca contained in the MnZn-based ferrite is less than 500 mass ppm in terms of CaCO3, the initial magnetic permeability of the MnZn-based ferrite in the high frequency band drops sharply. Therefore, the Ca contained in the MnZn-based ferrite is 500 mass ppm or more, preferably 700 mass ppm or more, in terms of CaCO3. On the other hand, when the Ca contained in the MnZn-based ferrite exceeds 1500 mass ppm in terms of CaCO3, abnormal grain growth is caused, and the initial magnetic permeability of the MnZn-based ferrite in the low frequency band is significantly reduced. Therefore, the Ca contained in the MnZn-based ferrite is 1500 mass ppm or less, preferably 1250 mass ppm or less, in terms of CaCO3.

[0031] Nb: 50~500 mass ppm Nb2O5 segregates at the grain boundaries and combines with Ca, which remains within the grains. 2+ The grain boundary is made highly resistive by attracting Nb2O5 to the grain boundary. Therefore, the inclusion of Nb2O5 reduces eddy current loss, maintains high normalized impedance in the high frequency band, and reduces residual magnetic flux density. If the amount of Nb contained in the MnZn ferrite is less than 50 mass ppm in terms of Nb2O5, the above effects cannot be sufficiently obtained. Therefore, the amount of Nb contained in the MnZn ferrite is 50 mass ppm or more in terms of Nb2O5, preferably 60 mass ppm or more, and more preferably 70 mass ppm or more. On the other hand, if the amount of Nb contained in the MnZn ferrite exceeds 500 mass ppm in terms of Nb2O5, abnormal grain growth occurs, leading to a decrease in the resistivity and initial permeability of the MnZn ferrite. Therefore, the amount of Nb contained in the MnZn ferrite is 500 mass ppm or less in terms of Nb2O5, preferably 400 mass ppm or less, and more preferably 350 mass ppm or less.

[0032] Bi:50~700 mass ppm Bi2O3 has the effect of promoting grain growth, and adding a small amount can significantly improve the initial magnetic permeability at room temperature. However, if the Bi contained in the MnZn ferrite is less than 50 mass ppm in terms of Bi2O3, the effect of improving the initial magnetic permeability cannot be sufficiently obtained. Therefore, the Bi contained in the MnZn ferrite is 50 mass ppm or more in terms of Bi2O3, preferably 75 mass ppm or more, and more preferably 100 mass ppm or more. On the other hand, if the Bi contained in the MnZn ferrite exceeds 700 mass ppm in terms of Bi2O3, abnormal grain growth occurs, leading to a decrease in the initial magnetic permeability. Therefore, the Bi contained in the MnZn ferrite is 700 mass ppm or less in terms of Bi2O3, preferably 650 mass ppm or less, and more preferably 500 mass ppm or less.

[0033] V:50~500 mass ppm V2O5 has a relatively low melting point and forms a liquid phase during sintering, which promotes densification of the crystals, improves the sintered density, and increases the saturation magnetic flux density. In addition, V2O5 forms Ca-V bonds near the grain boundaries, just like Nb2O5, and Ca 2+Segregates to the grain boundary to make the grain boundary highly resistive. The reduction of eddy current loss improves the normalized impedance in the high frequency band, resulting in a reduction in residual magnetic flux density. V2O5 has a greater effect on reducing residual magnetic flux density than Nb2O5. In addition, since the liquid phase sintering relaxes the distortion near the grain boundary, it is considered that the grain boundary stress is reduced and the residual magnetic flux density is reduced. If the V contained in the MnZn ferrite is less than 50 mass ppm in V2O5 conversion, the above effect cannot be sufficiently obtained. Therefore, the V contained in the MnZn ferrite is 50 mass ppm or more in V2O5 conversion, preferably 70 mass ppm or more, more preferably 80 mass ppm or more, and even more preferably 90 mass ppm or more. On the other hand, if the V contained in the MnZn ferrite exceeds 500 mass ppm in V2O5 conversion, the resistivity of the MnZn ferrite increases and the initial permeability is greatly reduced. Therefore, the V content in the MnZn-based ferrite is 500 ppm by mass or less, preferably 450 ppm by mass or less, more preferably 400 ppm by mass or less, and further preferably 350 ppm by mass or less, calculated as V2O5.

[0034] (Inevitable impurities) The composition of the present invention contains, in addition to the basic components and the subcomponents, unavoidable impurities, such as P, B, S, Cl, etc., and the total content of these unavoidable impurities is controlled to 500 ppm by mass or less.

[0035] (Porosity ratio within grain) If the number of pores occurring within the crystal grains relative to the total number of pores occurring in the MnZn ferrite, i.e., the pore ratio within the crystal grains, exceeds 20.0%, the initial permeability is insufficient. Therefore, the number of pores occurring within the crystal grains relative to the total number of pores occurring in the MnZn ferrite is set to 20.0% or less, and preferably 16.0% or less. On the other hand, there is no lower limit to the pore ratio within the crystal grains of the MnZn ferrite, and it may be 0.0%.

[0036] The pore ratio within the crystal grains of MnZn ferrite can be found as follows. The fracture surface of a MnZn ferrite sample is polished, and the grain boundaries are etched with fluoronitric acid. The etched fracture surface is observed at 200 to 500 times magnification using an optical microscope. The obtained image is analyzed, and the total number of pores generated within the crystal grains is divided by the total number of all remaining pores within the field of view to find the pore ratio within the crystal grains.

[0037] (crystal grain size) If the average crystal grain size of the MnZn ferrite is less than 16 μm, the movement of the domain walls is suppressed, and μi' (the real part of the initial permeability μi) at 10 kHz and 23°C decreases. Therefore, the average crystal grain size of the MnZn ferrite is set to 16 μm or more. On the other hand, if the average crystal grain size of the MnZn ferrite exceeds 25 μm, the impedance does not satisfy the desired value due to the decrease in grain boundary resistivity. Therefore, it is preferable that the average crystal grain size of the MnZn ferrite is 25 μm or less.

[0038] The crystal grain size of MnZn ferrite can be obtained as follows. A sample of MnZn ferrite is broken, and the cross section after breaking is observed with an optical microscope at a magnification of 400 times. The number of crystal grains included in this field of view is 1000 to 2000. The crystal grain size is calculated assuming that each observed crystal grain is a perfect circle, and the average value is obtained. For example, image analysis software "A-zo-kun" (registered trademark: manufactured by Asahi Kasei Engineering Co., Ltd.) may be used to calculate the crystal grain size.

[0039] (ΔB) The ΔB [mT] of MnZn ferrite is calculated by the following formula (1), and if it is less than 215 mT at 100°C, magnetic saturation is likely to occur. Therefore, the ΔB of MnZn ferrite is set to 215 mT or more at 100°C, and preferably 220 mT or more. On the other hand, the larger the ΔB of MnZn ferrite, the more preferable it is, and there is no particular upper limit. Conventionally manufactured MnZn ferrites generally have a saturation magnetic flux density of about 250 mT at 100°C, so ΔB is about 190 mT. ΔB=B m -B r (1) However, B m is the saturation magnetic flux density [mT], B r is the residual magnetic flux density [mT].

[0040] The saturation magnetic flux density of the MnZn ferrite at room temperature (rt) is preferably 450 mT or more, more preferably 490 mT or more, from the viewpoint of preventing magnetic saturation when a large current flows through the ferrite core. On the other hand, the higher the saturation magnetic flux density of the MnZn ferrite, the more preferable it is, and there is no particular upper limit.

[0041] The saturation magnetic flux density and residual magnetic flux density of MnZn ferrite can be determined as follows. A toroidal core is made from MnZn ferrite, and 40 turns of copper wire are wound on the primary side of the toroidal core, and 20 turns on the secondary side. Using a DC magnetization characteristic tester, the saturation magnetic flux density and residual magnetic flux density of the toroidal core are measured with a maximum magnetizing force H of 1200 A / m. ΔB can be determined from the obtained saturation magnetic flux density and residual magnetic flux density.

[0042] (Normalized impedance Z norm ) In this specification, the normalized impedance is a value obtained by normalizing the actually measured impedance by the dimensions and the number of turns of the coil. The normalized impedance Z of MnZn ferrite is norm [Ω mm -1 The Z of MnZn ferrite can be calculated in the frequency range of 500 kHz to 3 MHz by the following formulas (2) and (3). norm The maximum value at a frequency of about 1 MHz is 30 Ω mm -1 If the resistance is more than 1MHz, noise around 1MHz can be eliminated. norm is a maximum value of 30 Ω mm in the frequency range of 500 kHz to 3 MHz. -1 It must be at least 40Ω mm -1 It is preferable that the resistance is 45Ω·mm or more. -1More preferably, Z norm The maximum value is 50Ω mm -1 When the Z exceeds 500 kHz, norm Therefore, the Z of MnZn ferrite is norm is a maximum value of 50 Ω mm in the frequency range of 500 kHz to 3 MHz. -1 It is preferable that the inductance of the conventional MnZn ferrite, which has a high magnetic permeability, is low in the high frequency band. norm The maximum value of 20Ω·mm -1 That's about it. Z norm =Z c1 / N 2 (2) c1=l e / A e (3) where Z is the impedance [Ω] and c1 is the core constant [mm -1 ], l e is the magnetic path length [mm], A e is the cross-sectional area [mm 2 ], N is the number of turns of the coil [-]. The cross-sectional area is the area of ​​a cross section perpendicular to the circumferential direction of the toroidal core.

[0043] In addition, the Z of MnZn ferrite norm can be calculated as follows. Using an LCR meter (Keysight 4980A), measure the inductance L and quality factor Q of MnZn ferrite at 23°C from 1 kHz to 30 MHz. Based on these values, the standardized impedance Z is calculated by standardizing the initial permeability and core constant. norm Calculate.

[0044] (Initial permeability) From the viewpoint of removing noise due to inductance components, μi' (the real part of the initial permeability μi) of the MnZn ferrite is preferably 9000 or more at 10 kHz and 23° C., and 4000 or more at 500 kHz and 23° C. In addition, μi' of the MnZn ferrite is more preferably 4500 or more at 100 kHz and 23° C. On the other hand, if μi' of the MnZn ferrite is excessively high, the impedance Z at 1 MHz or higher decreases and noise cannot be removed. Therefore, μi' at 10 kHz and 23° C. is preferably 12000 or less. Similarly, μi' at 500 kHz and 23° C. is preferably 5000 or less.

[0045] The μi' of MnZn ferrite can be calculated as follows. A toroidal core is made from MnZn ferrite, and 10 turns of copper wire are wound around the toroidal core. The inductance L and quality factor Q of the toroidal core wound with copper wire are measured at 10 kHz in the range of -20 to 200°C using an LCR meter (Keysight 4980A), and μi' is calculated based on these values.

[0046] (Curie temperature) The Curie temperature of MnZn ferrite is set to 150°C or higher, taking into consideration the high temperature of the surrounding environment due to switching operations. On the other hand, there is no upper limit to the Curie temperature of MnZn ferrite, but it is usually set to 250°C or lower. The Curie temperature of MnZn ferrite can be calculated from the initial magnetic permeability.

[0047] (sintered density) The sintered density of MnZn ferrite is 5.00g / cm 3 If the saturation magnetic flux density is higher than this, a high ΔB can be obtained. Therefore, the sintered density of MnZn ferrite is 5.00 g / cm 3 On the other hand, the higher the sintered density of the MnZn ferrite, the better. There is no particular upper limit, but it is usually 5.10 g / cm. 3 That's about it.

[0048] (specific resistance) When the resistivity of MnZn ferrite is 10 Ω·cm or more, Z norm The frequency at which the resistivity reaches a maximum value shifts to the higher frequency side, and the maximum value becomes larger. Therefore, it is preferable that the resistivity of MnZn ferrite is 10 Ω·cm or more. On the other hand, if the resistivity of MnZn ferrite is 50 Ω·cm or less, a high initial permeability can be suitably obtained. Therefore, it is preferable that the resistivity of MnZn ferrite is 50 Ω·cm or less. The resistivity of MnZn ferrite can be obtained by the four-terminal method.

[0049] [Manufacturing method of MnZn ferrite] The method for producing MnZn-based ferrite according to the present invention includes a mixing and calcining step of mixing basic components to obtain a first mixture and calcining the first mixture to obtain a calcined product, a mixing and grinding step of adding and mixing an auxiliary component with the calcined product to obtain a second mixture and grinding the second mixture to obtain a pulverized product, a granulation step of adding and mixing a binder with the pulverized product, followed by granulation to obtain a granulated powder, a molding step of molding the granulated powder to obtain a molded body, and a sintering step of sintering the molded body under conditions in which the heating rate from 400°C to the maximum temperature is 50°C / hr or more and less than 300°C / hr, to obtain MnZn-based ferrite.

[0050] In the production of MnZn-based ferrite, first, the basic components Fe2O3, ZnO, and MnO powders are weighed out so as to obtain the above-mentioned ratio, and then mixed thoroughly to obtain a first mixture, which is then calcined (mixing and calcining step). In this case, the amount of unavoidable impurities is limited to the above-mentioned range. Mixing is preferably performed for about 16 hours using a wet ball mill. Calcination conditions are not particularly limited, but may be, for example, 925°C in air for 3 hours.

[0051] Next, the obtained calcined product is added with a predetermined ratio of subcomponents so that the content is as specified in the present disclosure, and mixed with the calcined powder and pulverized (mixing and pulverization process). In this process, the powder is sufficiently homogenized so that there is no bias in the concentration of the added components, and at the same time, the calcined powder is refined to the target average particle size to obtain a pulverized powder. The pulverization is preferably performed for 16 hours using a wet ball mill. In addition, the average particle size of the pulverized powder is preferably 1.15 μm to 1.25 μm.

[0052] Next, a known organic binder such as polyvinyl alcohol is added to the pulverized powder, and the mixture is granulated by a spray-drying method or the like to obtain a granulated powder (granulation step). If necessary, the mixture is passed through a sieve to adjust the particle size, and then molded under pressure in a molding machine to obtain a molded body (molding step).

[0053] Next, the molded body is fired to obtain MnZn-based ferrite (firing step). In the firing step, the heating rate from 400°C to the maximum temperature is 50°C / hr or more and less than 300°C / hr, so that the number of pores generated within the crystal grains can be 20.0% or less of the total number of pores generated in the MnZn-based ferrite. In addition, if the heating rate from 400°C to the maximum temperature in the firing step is less than 50°C / hr, sintering does not proceed, resulting in a decrease in sintered density and a decrease in initial permeability. Therefore, the heating rate from 400°C to the maximum temperature in the firing step is 50°C / hr or more, preferably 100°C / hr or more, and more preferably 150°C / hr or more. On the other hand, if the heating rate from 400°C to the maximum temperature in the firing step is 300°C / hr or more, the pores that were present at the grain boundaries before firing are incorporated into the grains as the grains grow, and remain as pores within the grains. Therefore, the rate of temperature rise from 400° C. to the maximum temperature in the firing step is less than 300° C. / hr, preferably 250° C. / hr or less, and more preferably 200° C. / hr or less.

[0054] If the maximum temperature in the sintering process is 1370°C or higher, the sintered density can be favorably obtained. Therefore, the maximum temperature in the sintering process is preferably 1370°C or higher. On the other hand, if the maximum temperature in the sintering process is too high, the amount of Zn evaporation increases, which greatly affects the composition fluctuation. Furthermore, the higher the sintering temperature, the larger the crystal grains grow, and the higher the initial permeability becomes, but the easier it is for eddy currents to flow within the grains, so the eddy current loss increases, and the initial permeability and normalized impedance in the high frequency band decrease. Therefore, the maximum temperature in the sintering process is preferably 1450°C or lower, and more preferably 1385°C or lower.

[0055] In addition, the longer the firing time, the higher the sintered density, which is preferable. Therefore, the firing time is preferably 2 hours or more. On the other hand, if the firing time is too long, the properties of the MnZn ferrite improve, but the productivity decreases. Furthermore, the longer the firing time, the larger the crystal grains grow, and the higher the initial permeability becomes, but the easier it is for eddy currents to flow within the grains, which increases eddy current loss and reduces the initial permeability and normalized impedance in the high frequency band. Therefore, the firing time is preferably 12 hours or less as a practical range, and more preferably 4 hours or less. Incidentally, firing may be performed in a state where a gas in which nitrogen gas and air are appropriately mixed is flowing.

[0056] The MnZn-based ferrite thus obtained simultaneously realizes excellent magnetic properties that were not possible with conventional MnZn-based ferrites, such as high initial permeability in the frequency band of about 10 to 500 kHz, large ΔB even at high temperatures such as 100°C, and a large maximum value of normalized impedance in the high frequency band of 500 kHz to 3 MHz.

[0057] Incidentally, the MnZn-based ferrite of the present invention can be produced by any conventional method unless otherwise specified in this specification. EXAMPLES

[0058] [Experimental Example 1] The raw powders were weighed so that the ratios of Fe2O3, ZnO and MnO were as shown in Table 1 when the iron, zinc and manganese contained were all converted as Fe2O3, ZnO and MnO. The raw powders were mixed for 16 hours using a wet ball mill and calcined in air at 925°C for 3 hours. Next, silicon oxide, calcium oxide, niobium oxide, bismuth oxide and vanadium oxide were added to the calcined powder so that the contents were as shown in Table 1 in terms of SiO2, CaCO3, Nb2O5, Bi2O3 and V2O5, respectively, and pulverized for 16 hours using a wet ball mill. After the pulverization, polyvinyl alcohol (PVA) was added to the pulverized powder obtained by drying, and the powder was granulated by passing through a sieve to obtain granulated powder. The granulated powder was formed into a toroidal shape to produce a green body, which was then introduced into a batch-type sintering furnace and heated from 400°C to the maximum temperature at a heating rate of 120°C / hr. The green body was then sintered at a maximum temperature of 1370°C for 2 hours in a gas flow of an appropriate mixture of nitrogen gas and air to produce a sintered toroidal core with an outer diameter of 30 mm, an inner diameter of 19 mm, and a height of 6 mm.

[0059] The sintered density of the toroidal core thus obtained was calculated by the Archimedes method at 23°C, and the resistivity was measured by the four-terminal method. Next, 10 turns of copper wire were wound around the toroidal core, and the inductance L and quality factor Q were measured in the range of -20 to 200°C at 10 kHz using an LCR meter (Keysight 4980A). The Curie temperature was calculated from the initial permeability calculated based on these values. Inductance L and quality factor Q were also measured in the range of 1 kHz to 30 MHz at 23°C, and the normalized impedance Z·c1 / N was normalized by the initial permeability and core constant based on these values. 2 was calculated.

[0060] The obtained toroidal core was wound with 40 turns of copper wire on the primary side and 20 turns on the secondary side, and the saturation magnetic flux density and residual magnetic flux density were measured using a DC magnetization characteristic tester with a magnetizing force H of up to 1200 A / m. From the measurement results, ΔB was calculated as the difference between the saturation magnetic flux density and the residual magnetic flux density.

[0061] Next, the pore ratio in the crystal grains of the MnZn ferrite was obtained. The fracture surface of the MnZn ferrite sample was polished, and the grain boundary was etched with fluoronitric acid. The etched fracture surface was observed at a magnification of 200 to 500 times using an optical microscope. The obtained image was analyzed, and the total number of pores generated in the crystal grains was divided by the total number of all remaining pores in the field of view to obtain the pore ratio in the crystal grains. In addition, the average crystal grain size of each example was measured as follows. The MnZn ferrite sample was broken, and the cross section after breaking was observed with an optical microscope at a magnification of 400 times. The crystal grain size was calculated assuming that each observed crystal grain was a perfect circle, and the average value was obtained. For example, image analysis software "A-zo-kun" (registered trademark: manufactured by Asahi Kasei Engineering Co., Ltd.) was used to calculate the crystal grain size.

[0062] As shown in Table 1, the addition of Nb2O5, Bi2O3 and V2O5 has an effect of improving the initial permeability, saturation magnetic flux density, ΔB and normalized impedance in the high frequency band.

[0063] [Table 1] [Industrial Applicability]

[0064] According to the present invention, it is possible to provide an MnZn-based ferrite having a high initial permeability in a wide frequency band of 10 to 500 kHz, a large ΔB even at a high temperature such as 100° C., and a large maximum value of normalized impedance in a high frequency band of 500 kHz to 3 MHz, and a method for producing the same.

Claims

1. An MnZn-based ferrite consisting of basic components, auxiliary components and unavoidable impurities, The basic components are Fe 2 O 3 The total of iron, zinc, and manganese calculated as ZnO and MnO is taken as 100 mol %, Iron: Fe 2 O 3 Converted to 51.0 mol % or more and 54.0 mol % or less, Zinc: 15.5 mol% or more and 21.0 mol% or less in terms of ZnO; and Manganese: Remainder and With respect to the basic component, the subcomponent is Si:SiO 2 Converted to 25 ppm by mass or more and less than 50 ppm by mass, Ca: CaCO 3 Converted to 500 ppm by mass or more and 1500 ppm by mass or less, Nb: Nb 2 O 5 Converted to 50 ppm by mass or more and 500 ppm by mass or less, Bi: Bi 2 O 3 50 ppm by mass or more and 700 ppm by mass or less in terms of total mass, and V:V 2 O 5 Converted to 50 ppm by mass or more and 500 ppm by mass or less Including, the number of pores occurring within crystal grains is 20.0% or less of the total number of pores occurring in the MnZn-based ferrite; An MnZn-based ferrite having an average crystal grain size of 16 μm or more.

2. 2. The MnZn-based ferrite according to claim 1, wherein the value of ΔB [mT] calculated by the following formula (1) is 215 mT or more at 100° C. ΔB=B m -B r ・・・(1) However, B m is the saturation magnetic flux density [mT], B r is the residual magnetic flux density [mT].

3. In the frequency range of 500 kHz to 3 MHz, the normalized impedance Z is calculated by the following formulas (2) and (3): norm [Ω mm -1 ] maximum value is 30 Ω mm -1 The MnZn-based ferrite according to claim 1 . Z norm =Z・c 1 / N 2 ・・・(2) c 1 =l e / A e ・・・(3) where Z is impedance [Ω], c 1 is the core constant [mm -1 ], l e is the magnetic path length [mm], A e is the cross-sectional area [mm 2 ], and N is the number of turns in the coil [-].

4. 2. The MnZn-based ferrite according to claim 1, wherein μi' (the real part of the initial magnetic permeability μi) at 10 kHz and 23° C. is 9000 or more, μi' (the real part of the initial magnetic permeability μi) at 500 kHz and 23° C. is 4000 or more, and the Curie temperature is 150° C. or more.

5. Sintered density is 5.00 g / cm 3 The MnZn-based ferrite according to claim 1 .

6. A method for producing the MnZn-based ferrite according to claim 1, comprising the steps of: a mixing and calcining step of mixing the basic components to obtain a first mixture and calcining the first mixture to obtain a calcined product; a mixing and grinding step of adding and mixing the auxiliary component with the calcined product to obtain a second mixture, and grinding the second mixture to obtain a ground product; A granulation step of adding and mixing a binder to the pulverized material, and then granulating the mixture to obtain a granulated powder; a molding step of molding the granulated powder to obtain a molded body; a firing step of firing the molded body under conditions in which the rate of temperature rise from 400° C. to the maximum temperature is 50° C. / hr or more and less than 300° C. / hr, thereby obtaining the MnZn-based ferrite; The present invention relates to a method for producing an MnZn-based ferrite having the above structure.

7. The method for producing MnZn-based ferrite according to claim 6, wherein the maximum temperature in the firing step is 1370°C or higher and 1450°C or lower.

Citation Information

Patent Citations

  • Mn-zn-based ferrite sintered compact and method for producing the same

    JP2003342062A

  • HEAT-RESISTANT HIGH MAGNETIC PERMEABILITY MnZn FERRITE

    JP2020132501A

  • MnZn-BASED FERRITE

    JP2022095537A

  • Oxide magnetic material having high saturation flux density and its manufacture

    JP1994283320A

  • Method for producing mnzn-based ferrite, mnzn-based ferrite, and ferrite core for power source

    JP2001342058A